Novel Point-of-Care Diagnostic Method for Neonatal Encephalopathy Using Purine Nucleosides - Beamer, Edward; O’Dea, Mary Isabel; Garvey, Aisling A.; Smith, Jonathon; Menéndez-Méndez, Aida; Kelly, Lynne; Pavel, Andreea; Quinlan, Sean; Alves, Mariana; Jimenez-Mateos, Eva M.; Tian, Faming; Dempsey, Eugene; et al. (Frontiers in Molecular Neuroscience, 2021)
Background: Evidence suggests that earlier diagnosis and initiation of treatment immediately after birth is critical for improved neurodevelopmental outcomes following neonatal encephalopathy (NE). Current diagnostic tests are, however, mainly restricted to clinical diagnosis with no molecular tests available. Purines including adenosine are released during brain injury such as hypoxia and are also present in biofluids. Whether blood purine changes can be used to diagnose NE has not been investigated to date. Methods: Blood purines were measured in a mouse model of neonatal hypoxia and infants with NE using a novel point-of-care diagnostic technology (SMARTChip) based on the summated electrochemical detection of adenosine and adenosine metabolites in the blood. Results: Blood purine concentrations were ~2-3-fold elevated following hypoxia in mice (2.77 ± 0.48 µM (Control) vs 7.57 ± 1.41 µM (post-hypoxia), p = 0.029). Data in infants with NE had a 2-3-fold elevation when compared to healthy controls (1.63 ± 0.47 µM (Control, N = 5) vs 4.87 ± 0.92 µM (NE, N = 21), p = 0.0155). ROC curve analysis demonstrates a high sensitivity (81%) and specificity (80%) for our approach to identify infants with NE. Moreover, blood purine concentrations were higher in infants with NE and seizures (8.13 ± 3.23 µM (with seizures, N = 5) vs 3.86 ± 0.56 µM (without seizures, N = 16), p = 0.044). Conclusions: Our data provides the proof-of-concept that measurement of blood purine concentrations via SMARTChip technology may offer a low-volume bedside test to support a rapid diagnosis of NE.